India's villages at cross-roads - Lakshminarayana, H.D. (New Delhi, 1976)
This volume focuses on the conditions and problems of rural people, their institutions and way of living, under the impact of planned social change, after the initiation of the Community Development Programme. Dr. Lakshmi narayana examines the impact of massive agricultural inputs on three villages in Mandya District, which were covered by the Intensive Agricultural District Programme (IADP); the changes due to the expanding communication network and the response of people to development programmes. He has care fully analysed the change and continuity in the villages with valuable data and insight. He has demonstrated that villagers cannot be taken for granted as irrational and tradition bound. The book gives some tips to planners, development ad ministrators and students of social change in village India.
Keywords: Social change